New TBAF complex, highly stable, facile and selective source for nucleophilic fluorination: applications in batch and flow chemistry - Said, Madhukar S.; Khonde, Nilesh S.; Thorat, Meghana N.; Atapalkar, Ranjit S.; Kulkarni, Amol A.; Gajbhiye, Jayant; Dastager, Syed G. (Asian Journal of Organic Chemistry, 2020)
Natural polysaccharides supported tetrabutylammonium fluoride (TBAF) complexes are prepared and found to be highly stable and selective fluoride source for well-renowned nucleophilic (SN2 type) fluorination reactions for the first time. Bacterial cellulose, plant cellulose, pectin, and starch derived TBAF complexes are synthesized, characterized (using SEM, TEM, and NMR techniques) and studied for their stability and reactivity. Heterogeneous bacterial cellulose-TBAF complex (NBu4(Bac-cell-OH)F) 1 was found to be highly stable and non-hygroscopic among all complexes, which gave high yields of fluorinated products in multi-gram scale in shorter reaction time. The primarily developed batch protocol was extended to solid-solid continuous flow reaction using an in-house built screw reactor, which furnished products in a few seconds of residence time (tR=20-25 sec) and excellent yields.
Keywords: Flow synthesis; fluorination; green chemistry; Sustainable Chemistry

Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Said, Madhukar S.; Udavant, Rohini; Sahu, Amit Kumar; Khan, Abujunaid; Nayak, Rashmi; Dastager, Syed G.; Kumar, Pradeep; Gajbhiye, Jayant (Natural Product Research, 2020)
The first total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate (butenolide cinnamate) was achieved using commercially available starting material. The synthesized compound was found to have promising antibacterial activity against Gram-negative strainsEscherichia coli(ATCC 8739),Salmonella typhimurium(ATCC 23564) andPseudomonas aeruginosa(ATCC 19154) with a minimum inhibitory concentration of 2.0 mu g/mL, 1.0 mu g/mL and 2.0 mu g/mL, respectively. Notably, the compound was more potent against Gram-negative test strains than the Gram-positive test strains.
Keywords: antibacterial activity; butenolide cinnamate; Total synthesis